2018
DOI: 10.1021/acsami.8b08125
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Loaded Self-Assembled Lipid Nanoparticles as Targeted Drug Delivery Systems for the Treatment of Aggressive Ovarian Cancer

Abstract: Chemotherapy using cytotoxic agents, such as paclitaxel (PTX), is one of the most effective treatments for advanced ovarian cancer. However, due to nonspecific targeting of the drug and the presence of toxic solvents required for dissolving PTX prior to injection, there are several serious side effects associated with this treatment. In this study, we explored self-assembled lipid-based nanoparticles as PTX carriers, which were able to improve its antitumour efficacy against ovarian cancer. The nanoparticles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 64 publications
9
76
1
Order By: Relevance
“…Numerous nanoparticle drug formulations are currently in development and evaluation stages in early and late-phase clinical trials [183]. These nanoparticles are loaded with ligands such as antibodies, peptides, aptamers for targeting various plasma membrane associated antigens on tumours, thus allowing formulations to be customized for patients [183,184].…”
Section: Nanoparticle Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous nanoparticle drug formulations are currently in development and evaluation stages in early and late-phase clinical trials [183]. These nanoparticles are loaded with ligands such as antibodies, peptides, aptamers for targeting various plasma membrane associated antigens on tumours, thus allowing formulations to be customized for patients [183,184].…”
Section: Nanoparticle Drug Deliverymentioning
confidence: 99%
“…Although this study provided a novel mechanism for focal adhesion kinase knockdown using a siRNA-formulated nanoparticle-based system to tackle chemoresistance in OC, other signaling pathways involved in chemoresistance mechanisms can be explored. Recently, we have shown that lipid-based cubosome formulated paclitaxel provides superior results in terms of greater reduction in tumour burden and increased progression-free survival in a mouse model of OC [184].…”
Section: Nanoparticle Drug Deliverymentioning
confidence: 99%
“…It has been reported that there exists an extremely high mortality rate in malignancies occurring in the genital tract of the female which includes cervical, ovarian, and endometrial cancers. This may result due to recurrence of cancer after persistence of minute residue of malignancy in the cells 28 . Therefore, in this study, we prepared coated cubosomes decorated with two hydrophobic anticancer drugs cisplatin and paclitaxel to study their efficacy against the HeLa cells, the most documented cell line of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…But taken in account the population density between two states, the prevalence were higher in Aljazeera state compared to Khartoum state 2:1 respectively (51). The second line platinum resistance chemotherapy include many type such as liposomal pegylated doxorubicin (55), topotecan (56), paclitaxel (57), oral etoposide (58) and gemcitabine (51). All of these chemotherapy agents have similar response treatment rate which is about 10 % (5).…”
Section: Discussionmentioning
confidence: 99%